Exploring the significance of WeChat in Chinese international students’ practice in the Australian higher education field - Meng, Xingyu; lisahunter (Journal of International Students, 2025)
WeChat is one of the most popular social media platforms amongst Chinese international students (CISs) studying in Australia, yet little is known about how its use mediates CISs transition to the Australian university. This study draws on Bourdieu’s concepts related to practice to explore CISs’ WeChat practices in digitally mediating their experiences in Australia. Data was collected from 15 CISs through semi-structured interviews with a scroll-back method. The findings suggest that CISs’ WeChat practice has deep roots in their habitus. WeChat was found to increase their sense of belonging and negotiation in the new international setting, but also diminished their successful transition. Moreover, the social media platform appeared to be underutilized by the university. The findings suggest that WeChat can be a more valuable tool for CISs to negotiate their transition, while CISs should also be guided to decrease their WeChat practice to more effectively engage with their higher education.